CUSTOMER LOYALTY: THE ROLE OF PRICE AND SERVICE QUALITY - Novi Susanti, Dwi; Djunaedi; Sudjiono (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
This study aims to determine the Effect of Price and Service Quality on Customer Loyalty at The Farrel Nganjuk Hotel. This study uses a quantitative approach with multiple linear regression analysis methods used to test the hypothesis after going through validity, reliability, and classical assumption tests. Data were obtained through distributing questionnaires to 58 respondents using the accidental sampling method. The results showed that Price and Service Quality have a positive and significant effect on Customer Loyalty. The more competitive the price offered and the better the quality of service provided, the higher the level of customer loyalty.